Level Kenyamanan Mahasiswa dalam Menggunakan Berbagai Kaidah Tangan Kanan (KTK) untuk Menyelesaikan Soal-Soal Gaya Lorentz - Yohanes Sudarmo Dua; Yohanes Yulianto; Kristiana Nathalia Wea (Departement of Mathematics Education, 2023)
This research is a descriptive study which aimed to describe the comfort level of respondents in applying each type of right-hand rule (RHR) to determine the direction of the Lorentz force (forward reasoning) and the direction of the velocity of a charged particle (backward reasoning) moving in a homogeneous magnetic field. The respondents of this study were 10 Pre-Service Physics teachers who were at 2nd, 4th and 6th semesters. The results showed that although each type of right-hand rule, when applied accurately, would show the same result, the comfort level of the respondents in applying each type the right hand rule (RHR) is different. This difference is influenced by the clarity and simplicity of the instructional description of each type of the RHR and the ease of matching or pairing the position of fingers (and also the palm) on each type of RHR with vectors positions. The study revealed that the right hand rule type III is the most preferable RHR for the majority of respondents (80%).